Caracterização bacteriológica da água do mar e diversidade de bactérias cultiváveis associadas ao coral Siderastrea stellata nos recifes costeiros de Cabo Branco, João Pessoa-PB - Araujo, Gilmara Henriques (2013)
Bacteria play a fundamental role in the health of corals. The interest in the study of microorganisms associated with corals has increased since the confirmation that they can be pathogenic or mutualistic. In the coastal reefs of the State of Paraiba the cases of the pigmentation changes of scleractinian Siderastrea stellata, that probably occurs in the process of coral bleaching, are observed. The aim of this work was to analyze the density and diversity of culturable bacteria associated with healthy and with pattern pigmentation altered (pink) colonies of coral S. stellata of coral reefs of Cabo Branco, João Pessoa - PB, as well as the physico-chemical and microbiological parameters of seawater in the study area over one year. Among the environmental variables (temperature, salinity, pH, dissolved oxygen, turbidity) of the reefs and beach water of Cabo Branco, only turbidity showed higher differences among the sites studied. The thermotolerant fecal coliforms, enterococci and Escherichia coli of seawater at the study sites were within the limits recommended for saline water class I (CONAMA 274/00). In general, the values of density of total heterotrophic bacteria and Vibrio spp. were significantly higher in the seawater during the months of December, January and February. According to the results of the partial sequencing of the 16S rRNA gene was found that bacteria isolated from healthy and pink S. stellata belonged to the classes Alpha-Proteobacteria and Gamma-Proteobacteria, and the variety of genera of bacteria were very different among the isolates from the two colonies. The high percentage of Vibrio spp., bacteria that are usually related to the diseases of corals, were observed among the isolates from pink colony.